Factors Affecting Compliance With Weight-Bearing Restriction and the Amount of Weight-Bearing in the Elderly With Femur or Pelvic Fractures - Seo, Hyeunsuk (Ann Rehabil Med, 2020)
OBJECTIVE: To determine the factors affecting the amount of weight-bearing during gait training in the elderly patients who underwent internal fixation after femur or pelvic fractures and how well they performed the weight-bearing restriction as directed by the physiatrist. METHODS: In this retrospective chart review study, we measured the amount of weight-bearing on the affected side in 50 patients undergoing internal fixation surgery and rehabilitation after femur or pelvic fracture using a force plate. Patients receiving non-weight-bearing or partial weight-bearing education were considered to perform weight-bearing restriction well when the amount of weight-bearing was <50 lb. Furthermore, regression analysis was performed to determine the effects of postoperative complications, age, cognitive function, and pain on weightbearing restriction. RESULTS: Variables affecting the amount of weight-bearing were age (r=0.581, p<0.001), weight-bearing education type (r=0.671, p<0.001), manual muscle strength of hip flexion on the non-affected side (r=-0.296, p=0.037), hip abduction (r=-0.326, p=0.021), knee extension (r=-0.374, p=0.007), ankle plantar flexion (r=-0.374, p=0.008), right hand grip strength (r=-0.535, p<0.001), Korean version of Mini-Mental State Examination (r=-0.496, p<0.001), Clinical Dementia Rating (r=0.308, p=0.03), and pain visual analog scale scores (r=0.318, p=0.024). The significant predictor of the amount of weight-bearing among these variables was age (β=0.448, p=0.001). The weight-bearing restriction adherence rate was significantly lower, at 22%, for patients aged ≥65 years as compared to 73% for those <65 years. CONCLUSION: Age was a major variable affecting the amount of weight-bearing. Compliance with weight-bearing restriction was significantly lower in patients aged ≥65 years than in patients <65 years.